Adoption of improved crop varieties by involving farmers in the e-wallet program in Nigeria. Issue 5 (3rd September 2018) - Uduji, Joseph Ikechukwu; Okolo-Obasi, Elda Nduka
ABSTRACT: The amount of improved seed used in Nigeria is extremely low. Overall, only 5–10% of cultivated land is planted with improved seeds, and about 10% of rural farmers use improved varieties. The objective of this investigation was to identify determinants of adoption of improved seed by farmers not participating in and those participating in the federal government's e-wallet program in Nigeria. We determined the impact of the e-wallet program on adoption of improved seed in rural areas. A total of 1200 rural farmers were sampled across six geopolitical zones of Nigeria. Results from the use of a bivariate probit model indicated that the e-wallet program continued to become increasingly popular among rural farmers; and that farmers' literacy, ownership of a mobile phone, value output, mobile network coverage, power for charging phone batteries and contact with extension agents were the positive determinants of farmer participation in the e-wallet program. Cultural obstacles to married women, growers' age, and increased distance to registration and input collection centers reduced farmers' tendency to participate in the e-wallet program. The results also showed that rural farmers depended on the e-wallet program for increased use and adoption of improved seed in Nigeria, to boost food security in sub-Saharan Africa. The results suggested the need for an improved e-wallet model by lessening constraints mostly associated with rural information and communication infrastructure, and distance to the registration and input collection centers.